Material counter-cartographies: (Un)mapping (in)justice, spatial wounding, and abstract reticulations. Issue 9 (21st October 2021) - Varga, Bretton A.; Agosto, Vonzell; Maguregui, Julian
Abstract: This article takes an arts-based approach to unmasking the (wounded) naming histories of public schools within a 20-miles radius of a university in central Florida. It applies an artistic methodology that was inspired by the abstract artwork of Mark Bradford. Through the application of this methodology (e.g. research, layer, excavate), the authors created two maps—counter-cartographies—to accentuate the problematic undertow of schooling through names couched in coloniality. Notwithstanding our findings into material articulations (i.e. counter-cartographies), this research suggests that (teacher) educators could benefit from reimagining the potentiality of mapping practices and how cartographies can be used to (spatially) express masked history/ies within the context of place-based naming practices.